Seasonality in Nutrient Contents of Edible Green Algae Ulva compressa and Ulva fasciata from Southeast Coast of India - N. Monisha Hyderali; Ganesan, M.; Eswaran, K. (Asian Journal of Engineering and Applied Technology, 2019)
Seasonal variations in the proximate (protein, carbohydrate, dietary fiber, ash, moisture, lipid, amino acid and fatty acid content), mineral composition (Na, K, Ca, Mg, Fe, Zn, C, Mn) and Heavy metals content (Cd, Pb, Hg and Ni) of Ulva compressa and Ulva fasciata were investigated for all four different seasons (Spring, North east monsoon, Summer and South west monsoon) during 2015 to 2016. Data were analyzed using one- and two-way ANOVA. Significant variations in the proximate constituents were found among seasons and species. Maximum proximate and mineral composition in U. compressa are protein, carbohydrate, ash content, moisture content and lipid in northeast monsoon, dietary fiber, amino acids content and mineral content in southwest monsoon, fatty acids content in spring. Heavy metals were not detected except lead. In U. fasciata, maximum proximate and mineral composition are protein, carbohydrate, moisture content, ash content in spring season, dietary fiber in summer season, lipid and total amino acids content in northeast monsoon, fatty acids contents and mineral content in southwest season. Heavy metals were not detected except lead. U. compressa has highest protein, carbohydrate, moisture content, amino acids and mineral content as compared to U. fasciata. U. fasciata has maximum dietary fiber, ash content, lipid content and fatty acids as compared to U. compressa. In general, Northeast monsoon showed the highest proximate and mineral composition in both the algae. The present study revealed that these two edible algae have higher proximate contents which can be more ideal for food consumption for humans and animals.